ANALISIS PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES UNTUK PEMBELAJARAN DI SEKOLAH - Tiarani, Siti Dhinda; Firman; Desyandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to explore and analyze the development of Google Sites-based learning media for school education, incorporating 21st-century learning approaches. The method used in this study is the Systematic Literature Review (SLR) to identify, review, evaluate, and interpret all available research on the topic of interest. By using the SLR method, a systematic review and identification of journals can be conducted. Data were collected by searching various articles in online journals with the help of Google Scholar. The articles collected were only those published between 2021 and 2024. From the various articles, the researcher selected 8 that were closely related to the keywords used. The conclusion of this research indicates that Google Sites-based learning media has significant potential in creating engaging and effective learning experiences, supporting remote learning, and meeting modern educational needs.